The Efficiency of the Role of Marketing Mix in Smartphone Business - munandar, Dadang; Indriani, Dewi; Merdiani, Wentri; Rubedo, Hendar; Jamilah, Nur (KnE Social Sciences, 2024)
Technology is evolving swiftly in the modern day, especially in communication. One instrument that is used on a global scale is the smartphone. The purpose of this study is to evaluate the marketing mix’s effectiveness at the X smartphone store. This study uses a descriptive qualitative design to investigate the current state of a class of current occurrences, an object, a condition, or a human group. In this study, inductive was utilized by the researchers to examine, evaluate, and derive conclusions from field phenomena. The productivity of the business will demonstrate how well the marketing mix was implemented. When it comes to luring clients or consumers to the store for all their smartphone needs and accessories, the deployment of a marketing mix marketing approach is seen to be highly successful. Additionally, the X smartphone store’s advertising team consistently develops fresh, inventive ways to market smartphone products in an effort to draw in more customers and help the business succeed in the long run. Keywords: marketing mix, smartphone, business